PENERAPAN FITUR AUTOCOMPLETE DAN ALGORITMA TURBO BOYER MOORE PADA APLIKASI KAMUS KIMIA - Novina, Firda; Darmanto, Tony; Antonius, Antonius (INTEKSIS, 2024)
This research implements the autocomplete feature and the Turbo Boyer Moore algorithm on an Android-based chemical term dictionary application. The autocomplete feature allows users to quickly search for chemical terms by entering only the first few letters, while the Turbo Boyer Moore algorithm is used for efficient string matching. This research uses data collection techniques, object-oriented system analysis, and application design techniques using Android Studio and SQLite. The result is an Android-based chemical term dictionary application that speeds up the search process and display relevant word suggestions. The conclusion that researchers can give from the results of applying the autocomplete feature and the Turbo Boyer Moore algorithm in this chemical term dictionary application is that it can search quickly and accurately, and minimizes time in typing patterns. The author gives advice to readers to be able to add other features such as the autocorrect features, voice recognition and can combine it with other algorithms. Keywords: Turbo Boyer Moore Algorithm, Autocomplete, Dictionary, Chemical Term Dictionary